Cancer prevalence in United States, Nordic Countries, Italy, Australia, and France: An analysis of geographic variability - Crocetti E.; De Angelis R.; Buzzoni C.; Mariotto A.; Storm H.; Colonna M.; Zanetti R.; Serraino D.; Michiara M.; Cirilli C.; Iannelli A.; Mazzoleni G.; et al. (British Journal of Cancer, 2013)
Background:The objectives of this study were to quantitatively assess the geographic heterogeneity of cancer prevalence in selected Western Countries and to explore the associations between its determinants.Methods:For 20 cancer sites, 5-year cancer prevalence, incidence, and survival were observed and age standardised for the mid 2000s in the United States, Nordic European Countries, Italy, Australia, and France.Results:In Italy, 5-year crude prevalence for all cancers was 1.9% in men and 1.7% in women, while it was âˆ1⁄41.5% in all other countries and sexes. After adjustment for the different age distribution of the populations, cancer prevalence in the United States was higher (20% in men and 10% in women) than elsewhere. For all cancers combined, the geographic heterogeneities were limited, though relevant for specific cancers (e.g., prostate, showing >30% higher prevalence in the United States, or lung, showing >50% higher prevalence in USA women than in other countries). For all countries, the correlations between differences of prevalence and differences of incidence were >0.9, while prevalence and survival were less consistently correlated.Conclusion:Geographic differences and magnitude of crude cancer prevalence were more strongly associated with incidence rates, influenced by population ageing, than with survival rates. These estimates will be helpful in allocating appropriate resources. Â© 2013 Cancer Research UK. All rights reserved.